The Relationship Between Total Quality Management and Customer Satisfaction Through the Mediation of Employee Performance - Parhan, Mario; Bakhtiar, Arfan (Department Industrial Engineering, University of Muhammadiyah Malang, 2024)
The increasing competition in the global market, driven by globalization and technological advancements, has caused many companies to face challenges in maintaining their market position. As a result, effective quality management systems are essential to enhancing employee performance and delivering high-quality products and services to satisfy customers. This study aims to analyze the effect of Total Quality Management (TQM) implementation on employee performance, the influence of employee performance on customer satisfaction, and the mediating role of employee performance between TQM and customer satisfaction. The research was conducted on companies certified with ISO 9001:2015, using questionnaires filled out by 80 respondents. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that TQM significantly improves employee performance, positively affecting customer satisfaction. Additionally, TQM directly enhanced customer satisfaction, with employee performance as an effective mediator in this relationship. These findings suggest that improving TQM practices and employee performance can substantially increase customer satisfaction. The study provides recommendations for companies in Indonesia to optimize TQM implementation, aiming to enhance both employee performance and customer satisfaction.